Adjustment of Eculizumab Dosage Pattern in Patients with Atypical Hemolytic Uremic Syndrome with Suboptimal Response to Standard Treatment Pattern. (29th November 2016) - García Monteavaro, Camino; Peralta Roselló, Carmen; Quiroga, Borja; Baltar Martín, José María; Castillo Eraso, Lorena; de Álvaro Moreno, Fernando; Martínez Vea, Alberto; Visus-Fernández de Manzanos, María Teresa
Abstract : In patients with atypical hemolytic uremic syndrome (aHUS), complement blocking by eculizumab rapidly halts the process of thrombotic microangiopathy and it is associated with clear long-term hematologic and renal improvements. Eculizumab treatment consists of a 4-week initial phase with weekly IV administration of 900 mg doses, followed by a maintenance phase with a 1, 200 mg dose in the fifth week and every14 ± 2 days thereafter. We present three patients with aHUS and suboptimal response to eculizumab treatment at the usual administration dosage who showed hematologic and renal improvements after an adjustment in the eculizumab treatment protocol.